Antioxidant and Neuroprotective Effects of Paeonol against Oxidative Stress and Altered Carrier-Mediated Transport System on NSC-34 Cell Lines - Sana Latif; Seung-Hye Choi; Asmita Gyawali; Seung Jae Hyeon; Young-Sook Kang; Hoon Ryu (Antioxidants, 2022)
Paeonol is a naturally occurring phenolic agent that attenuates neurotoxicity in neurodegenerative diseases. We aimed to investigate the antioxidant and protective effects of paeonol and determine its transport mechanism in wild-type (WT; NSC-34/hSOD1WT) and mutant-type (MT; NSC-34/hSOD1G93A) motor neuron-like amyotrophic lateral sclerosis (ALS) cell lines. Cytotoxicity induced by glutamate, lipopolysaccharides, and H2O2 reduced viability of cell; however, the addition of paeonol improved cell viability against neurotoxicity. The [3H]paeonol uptake was increased in the presence of H2O2 in both cell lines. Paeonol recovered ALS model cell lines by reducing mitochondrial oxidative stress induced by glutamate. The transport of paeonol was time-, concentration-, and pH-dependent in both NSC-34 cell lines. Kinetic parameters showed two transport sites with altered affinity and capacity in the MT cell line compared to the WT cell line. [3H]Paeonol uptake increased in the MT cell line transfected with organic anion transporter1 (Oat1)/Slc22a6 small interfering RNA compared to that in the control. Plasma membrane monoamine transporter (Pmat) was also involved in the uptake of paeonol by ALS model cell lines. Overall, paeonol exhibits neuroprotective activity via a carrier-mediated transport system and may be a beneficial therapy for preventing motor neuronal damage under ALS-like conditions.